Attitude of Secondary School Teachers towards the Use of Information Communication Technology: - (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The training framework is the primary wellspring of human asset advancement. Its emphasis is on the obtaining of information, self-learning, conventional and adaptable abilities in communication, business venture, the board and technology that are the attributes of the learning society of today. Information and communication technologies (ICT) has arisen as one of the main parts of human existence and it has impacted each part of school working including organization, time table, example conveyance, project work, assessment, assessment framework and so on ICT have made teaching-learning process more important for the student and associated with reality. In present review, attitude of secondary school teachers of Buxar district towards the utilization of information communication technology in training was contemplated.